KZ-PROFESI: DEVELOPMENT OF PROFESSION ZAKAT CALCULATING APPLICATION FEATURES AND SERVICES - Hidayah, Eni Zulfa; Rozikin, Zainur; Agustiningsih, Maulida Dwi; Adnan, Fahrobby (UIN Sunan Kalijaga, 2024)
Indonesia has a huge potential for zakat, given that the majority of its population is Muslim. This potential comes from various types of zakat, such as zakat fitrah, zakat maal, professional zakat, and infaq and sadaqah. This research aims to develop professional zakat application features and services that can help people understand and calculate the amount of professional zakat. The research uses the 4D approach: Define, Design, Develop, and Disseminate. The user needs definition phase is carried out through a literature review. Before the application development, design is conducted using Use Case diagrams and Flow screen diagrams. The application is developed using Kodular and implemented on Android smartphones. Testing is performed using black box testing for functional and System Usability Scale (SUS) testing for non-functional requirements. The functional testing results show that the application's primary function successfully calculates professional zakat. The results of the non-functional testing using SUS indicate that the application is categorized as good. =============================================== Indonesia memiliki potensi zakat yang sangat besar, mengingat mayoritas penduduknya beragama Islam. Potensi ini berasal dari berbagai jenis zakat, seperti zakat fitrah, zakat maal, zakat profesi, serta infaq dan sedekah. Penelitian ini bertujuan untuk mengembangkan fitur dan layanan aplikasi zakat profesi yang dapat membantu masyarakat dalam memahami dan menghitung besaran zakat profesi. Penelitian menggunakan pendekatan 4D: Define, Design, Develop, dan Disseminate. Tahap pendefinisian kebutuhan pengguna dilakukan dengan studi literatur. Sebelum pembuatan aplikasi, dilakukan desain menggunakan diagram Usecase dan Flowscreen. Pengembangan aplikasi menggunakan Kodular dan diimplementasikan pada smartphone Android. Pengujian dilakukan dengan menggunakan pengujian black box untuk kebutuhan fungsional dan pengujian System Usability Scale (SUS) untuk kebutuhan non fungsional. Hasil pengujian fungsional menunjukkan bahwa fungsi utama aplikasi telah berhasil menghitung zakat profesi. Hasil pengujian non fungsional menggunakan SUS menunjukkan bahwa aplikasi termasuk dalam kategori baik.